1998
DOI: 10.1038/sj.onc.1201554
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two distinct deleted regions on chromosome 13 in prostate cancer

Abstract: Aberrations of 13q occur frequently in prostate cancer and this chromosome contains two known tumor suppressor genes, BRCA2 and Rb1. This study analysed 13q LOH, DNA ploidy, BRCA2 mutation and pRb expression in prostate cancers. In total, 13q deletions were found in 18 of 36 tumors but did not correlate with histological grade, stage or DNA ploidy. Two smallest regions of overlapping deletions were de®ned: one¯anked by D13S218 and D13S153; the other¯anked by D13S31 and D13S137. BRCA2 was less frequently delete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
5

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 19 publications
4
58
5
Order By: Relevance
“…A comparative genomic hybridization (CGH) study reported allele losses in 32% of untreated primary tumors and in 56% of locally progressive primary tumors after hormonal therapy (Visakorpi et al, 1995). A wide range (9 ± 48%) of loss of heterozygosity (LOH) in the chromosomal region that includes the retinoblastoma (RB) TSG locus, on chromosome 13q14, were reported in several studies (Carter et al, 1990;Kunimi et al, 1991;Cooney et al, 1996;Cunningham et al, 1996;Li et al, 1998). However, con¯icting results were reported regarding the involvement of the RB TSG in prostate cancer.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…A comparative genomic hybridization (CGH) study reported allele losses in 32% of untreated primary tumors and in 56% of locally progressive primary tumors after hormonal therapy (Visakorpi et al, 1995). A wide range (9 ± 48%) of loss of heterozygosity (LOH) in the chromosomal region that includes the retinoblastoma (RB) TSG locus, on chromosome 13q14, were reported in several studies (Carter et al, 1990;Kunimi et al, 1991;Cooney et al, 1996;Cunningham et al, 1996;Li et al, 1998). However, con¯icting results were reported regarding the involvement of the RB TSG in prostate cancer.…”
Section: Introductionmentioning
confidence: 67%
“…In PC, the most frequent allele losses have been detected on chromosomes 7q, 8p, 10q, 13q, 16q and 18q (Visakorpi et al, 1995;Carter et al, 1990;Kunimi et al, 1991;Bergerheim et al, 1991;Bova et al, 1993;Zenklusen et al, 1995;MacGrogan et al, 1994;Trapman et al, 1994;Kagan et al, 1995;Suzuki et al, 1995;Macoska et al, 1995;Cooney et al, 1996;Latil et al, 1995;Cunningham et al, 1996;Li et al, 1998). However, except for the chromosome 10q23 gene, MMACI/PTEN, a candidate TSG in the very advanced stage of PC, no candidate TSGs has been cloned Li et al, 1997;Teng et al, 1997;Cairns et al, 1997;Suzuki et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of RB has been found in a subset of prostate carcinomas (Bookstein et al, 1990). However, the absence of mutations in both the RB1 and the BRCA2 gene indicated to several authors (Cooney et al, 1996b;Li et al, 1998) that tumor suppressor genes other than RB1 or BRCA1 may be the target of 13q deletions.…”
Section: Chromosomal Lossesmentioning
confidence: 99%
“…Likewise other examples correlating chromosome 13 to prostate cancer include LOH involving the long arm of chromosome 13 in as many as a third of prostate cancers (Cooney et al, 1996;Li et al, 1998). Microsatellite marker analysis indicated that loss of BRCA2 was relatively uncommon in localized prostate cancer but deletion of Rb was more frequent in long arm of chromosome 13 (Li et al, 1998).…”
Section: Discussionmentioning
confidence: 99%